IN VITRO ANALYSIS OF ANTIMICROBIAL COMPOUNDS FROM ALSTONIA SCHOLARIS - Abraham, Jayanthi; Chakraborthy, Pritha; Chand, Aakanksha; Srivastava, Shagun; Yadav, Ramesh; Kingsley, Dannie (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The increasing prevalence of drug-resistant pathogens has gained the attention of pharmaceutical and scientific communities toward potential antimicrobial agents from plant-derived sources. The present work deals with the extraction, screening, and characterization of antimicrobial compounds from Alstonia scholaris against various pathogenic micro-organisms. Methods: The components of crude extracts obtained after soxhlet extraction of plants were characterized through thin layer chromatography (TLC) and gas chromatography-mass spectrometry (GC-MS). The antimicrobial effect was checked at different concentration against Bacillus subtilis MTCC 121, Staphylococcus aureus MTCC 96, Escherichia coli MTCC 43, Klebsiella pneumonia MTCC 432, Pseudomonas aeruginosa MTCC 424, and Streptococcus pyogenes MTCC 497. Results and Conclusion: A. scholaris extract showed a significant antibacterial effect against selective pathogens. The bioactive compounds were separated and identified by TLC and GC-MS, respectively. Keywords: Bioactive metabolites, Extraction, Bioactivity, Pathogens, Minimum inhibitory concentration.